Weekly Water Balances of Normal and Severe Drought Years at Dharwar - Ratnam, B P; Joshi, S N (Annals of Arid Zone, 2016)
A comparative study was made of the weekly water balances, for the Kharif season, of the normal and severe drought years, at a dry humid station, Dharwar. In the drought year, water deficiency occurred during 12 out of the 17 weeks of rainy season, whereas the corresponding figures for a normal year were 5 out of 17 weeks. The role of a 3 -week spell of above normal rains, after a prologned period of water deficiency of saving the Kharif crop was limited.